Internalisasi nilai “ilir-ilir” pada pendidikan akuntansi: Dari “sandang” menuju “ageman” - Darti Djuharni; Sonhaji Sonhaji; Nur Alimin Azis (Imanensi: Jurnal Ekonomi, Manajemen, dan Akuntansi Islam, 2019)
This article aims to explore the poetical value "Ilir-Ilir", has a Javanese culture style, to be articulated in the development of accounting education. The phenomenon of accounting practices in Indonesia that deviates from propriety and goodness, should make academics and accounting practitioners aware of the solution. Data is collected through reading the literature to explore the value of poetry "ilir-ilir". Data analysis uses Self as the main analysis tool with the help of Barthes Semiotics research method. The analysis is carried out through two levels of significance, namely denotation analysis and connotation, myth and symbol analysis. This research succeeded in uncovering the value of the poetry "Ilir-Ilir", so that concepts and principles can be identified that should smear accounting education in Indonesia.